Outcomes following abdominal sacrocolpopexy for pelvic organ prolapse - Rawat, Anushree; Garg, Ruchika; Yadav, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hysterectomy is one of the most performed surgical procedures during lifetime. Almost 10% of women who have had a hysterectomy because of prolapse symptoms. Sacrocolpopexy (sacral colpopexy) is a surgical technique to repair pelvic organ prolapses. Specifically, it is intended to address apical or vaginal vault prolapse in women with lower perioperative morbidity, shorter hospital stay and allows a long-term anatomical restoration. It provides excellent apical support with lower rate of recurrence. Aim of present study was to assess the efficiency of conventional method of sacrocolpopexy and to assess the follow up complaints of patients. Methods: This study is conducted in maternal and child health wing of Sarojini Naidu medical college from June 2019 till December 2019. Sacrospinous fixation was performed with conventional needle holder as compared to Miya hook. Data were collected from participants using a structured questionnaire. Follow up was conducted at 6 weeks and 12 weeks. Results: In this study there were 43.3% pre menopausal patients and 53.6% menopausal patients. Maximum patients were multiparous i.e. para 2 (36.6%). Maximum patient belongs to POP Q stage 3. After 6 weeks of surgery maximum patients had pain in abdomen i.e. 3.33%, dyspareunia 8.33% and 100% success rate of sacropexy. Conclusions: Sacrocolpopexy is a cost effective and safe procedure with high anatomical cure and patient satisfaction rate and low intra-operative and. postoperative complications as well as recurrence rates.